INDUSTRI 4.0: PENGUKURAN TINGKAT KESIAPAN INDUSTRI TEKSTIL DENGAN METODE SINGAPORE SMART INDUSTRY READINESS INDEX - Satrio Utomo; Nugraheni Setiastuti (Jurnal Techno Nusa Mandiri, 2019)
The era of technology is disrupted at this time, better known as the Industrial Revolution 4.0, already been applied to a various field of each country. Industry 4.0 include Internet of Thing (IoT), Artificial Intelligence (AI), human-machine interface, 3-D printing, and Advanced Robotics. Industry 4.0 is expected to increase productivity, business efficiency, and competitiveness. Indonesia’s Ministry of Industry has designed ‘Making Indonesia 4.0’ by preparing a roadmap and strategy to meet industry 4.0. There are 5 (five) prioritize manufacturing industrial sectors: Food and Beverages, Textile and Apparel, Electronics, Chemical, and Automotive. For studies conducted in the textile and apparel industry, as one of the priority industries. The Research study was conducted to determine the level of readiness of the textile manufacturing industry to meet industry 4.0 based on aspects of Technology, Processes, and Organizations. The method used is The Singapore Smart Industry Readiness Index. By knowing this level of readiness, it will help the industry to know the position of the current level of readiness and what needs are needed to reach the level of industry 4.0. By knowing the position, is able to know the strengths and weaknesses of technology from the operational technology used, which then knows the technological priorities that are of concern by management to increase industrial competitiveness towards industrial level 4.0.Based on the results of the mapping, related to the level of readiness of the textile industry of PT. Grand Textile based on technological aspects (1.56), process aspects (1.33) and organizational aspects (2.00) amounted to 1.63; position at level 1 which is categorized as New Comer.